2020
DOI: 10.1140/epjb/e2020-100549-0
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in the Kondo-lattice

Abstract: We discuss the ferromagnetic phase of the planar Kondo lattice model using the bond fermion technique. For sufficiently small Kondo exchange we find a weakly ferromagnetic phase already for the weakly doped Kondo insulator. We present the phase diagram of the model and its quasiparticle band structure in the different phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Previous studies [52][53][54][55][56][57][58][59][60][61] have shown that a ferromagnetic phase exists in the SU(2)-symmetric Kondo lattice model for low-filled c electrons at zero temperature. Our results obtained here show that a ferromagnetic phase with magnetization in the x-direction exists even for weak Rashba-type SOC in the periodic Anderson model.…”
Section: B Ferromagnetismmentioning
confidence: 99%
“…Previous studies [52][53][54][55][56][57][58][59][60][61] have shown that a ferromagnetic phase exists in the SU(2)-symmetric Kondo lattice model for low-filled c electrons at zero temperature. Our results obtained here show that a ferromagnetic phase with magnetization in the x-direction exists even for weak Rashba-type SOC in the periodic Anderson model.…”
Section: B Ferromagnetismmentioning
confidence: 99%